Trabecular Bone Score and Bone Quality in Systemic Lupus Erythematosus Patients - Ruaro, Barbara; Casabella, Andrea; Paolino, Sabrina; Alessandri, Elisa; Patané, Massimo; Gotelli, Emanuele; Sulli, Alberto; Cutolo, Maurizio (Frontiers in Medicine, 2020)
Background Systemic lupus erythematosus (SLE) patients run a higher risk of having low bone mass due to multi-factorial events that include, physical inactivity, persistent inflammation, low vitamin D levels and glucocorticoid treatment. This study aimed at obtaining a comparison between bone involvement in SLE patients and healthy matched subjects (HS). Methods A total of 40 SLE females (average age 54.1±16.3 years) and 40 age-gender matched HS (average age 54.2±15.9 years) were enrolled after having obtained informed written consent. Bone Mineral Density (BMD, g/cm2) of the lumbar spine (L1-L4) was analyzed by a DXA scan (GE, Lunar Prodigy). The lumbar spine TBS was derived for each spine DXA examination by the TBS index (TBS iNsight Medimaps). Results The lumbar spine TBS score was statistically significantly lower in SLE patients than in HS (0.797±0.825 vs 1.398±0.207, p-value< 0.001, as was mineral density (BMD) (p-value<0.001), in all areas examined. Conclusions SLE is associated with significant low bone mass, as evidenced by dual-energy X-ray absorptiometry (DXA) and the trabecular bone score (TBS). This study emphasizes the importance of using DXA and TBS in the evaluation of the different aspects of bone architecture.